Acute cytotoxicity and increased vascular endothelial growth factor after in vitro nitrogen mustard vapor exposure. Issue 1 (14th May 2020) - McGraw, Matthew D.; Kim, So‐Young; White, Carl W.; Veress, Livia A.
Abstract: Nitrogen mustard (NM) is a highly toxic alkylating agent. Inhalation exposure can cause acute and chronic lung injury. This study's aims were to develop an in vitro coculture model of mustard‐induced airway injury and to identify growth factors contributing to airway pathology. Primary human bronchial epithelial cells cultured with pulmonary endothelial cells were exposed to NM (25, 50, 100, 250, or 500 μM) or PBS (control) for 1 hour. Lactate dehydrogenase (LDH) and transepithelial electrical resistance (TEER) were measured before and 24 h after NM exposure. Fixed cultures were stained for hematoxylin and eosin or live/dead staining. Culture media were analyzed for 11 growth factors. A 1‐h vapor exposure to greater than or equal to 50 μM NM increased supernatant LDH, decreased TEER, and caused airway epithelial cell detachment. Endothelial cell death occurred at 500 μM NM. Vascular endothelial growth factor A (VEGF‐A) and placental growth factor (PlGF) expression increased in 500 μM NM−exposed cultures compared with PBS‐exposed control cultures. NM vapor exposure causes differential cytotoxicity to airway epithelial and endothelial injury in culture. Increased VEGF‐A and PlGF expression occurred acutely in airway cocultures. Future studies are required to validate the role of VEGF signaling in mustard‐induced airway pathology. Abstract : The in vitro model of primary airway epithelial and endothelial cells at the air–liquid interface closely models the injury seen after an acute mustard inhalation injury with acute cytotoxicity at increasing NM concentrations. Two important growth factors, VEGF‐A and PlGF, related to pulmonary vascular biology and angiogenesis were increased at 24 h after a single‐hour NM vapor exposure. Future in vivo and in vitro studies are required to validate the use of VEGF‐A or PlGF as a potential biomarker or drug therapy for either acute or chronic vascular pathogenesis after high‐concentration mustard inhalation exposure.